The optimization of the coaching of the junior handball players according to the demands of modern training - Maihaila, I.; Iancu, A.; Cretu, M.; Mihailescu, N. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The sportive training as well as the motivation in the sportive practice led to the apparition of phenomena and stuations necessary to the creation of some precise methodologies regarding the sportive training, from the initiation of the children and juniors to that of the performance and high performance sportsmen. Considering the complexity acquired by the coaching of sportsmen, as a result of the increase of their performances, we mention that the optimization of this process implies, besides the factors of the sportive training, numerous factors of organizational nature, medical and material base, which are meant to amplify their sphere, clearly exceeding the one specific to an instructive-educational process. METHODS The measurements and the experiments have been made all along a competitional year as part of the preliminary experiment on a number of 392 junior handball players, participants in the National Championship, 14 sportsmen of the National group at the same category of age and 14 handballers from the Moreni Petrol High school (all between the ages of 15 and 16), handball players which subsequently became components of the experimental group. The training curriculum suggested by us for the components of the experimental group has been applied along all the stages of training (respecting each one`s objectives) during a competitional year. The experiment began in August at the same time with the initial testing (T.I.) and ended in May, when the final testing (T.F.) took place for 18 indicators: 3 functional, 5 of general physical training, 5 of specific physical training and 5 of technical training. At the end of the experiment the results obtained by the components of the two groups have been elaborated and interpreted statistically-mathematically, on the basis of which conclusions and suggestions for the technicians have been formulated. CONCLUSION The conclusions of the paper include in great measure the order in which the scientific investigations have been realized and centralized on the constitutive elements of the work hypothesis that they abundantly confirm. The training of a junior handball player must allocate a great deal to the physical training, being known the fact that the purpose of this is determined not only in the development of the technical and tactical qualities, but also, in the perfecting of the big functions of the organism and of morphofunctional indices. To the echelons of juniors, the planning of the content of the physical preparation must take into account the complex character in which the motive qualities in the game of handball are demonstrated. The analysis and re-thinking, through the viewpoint of the activities typical to the didactic projection inscribed on the praxiological circuit, are imposed: oectives-contents-strategies-evaluation, of all the organizational forms of display of the training process, in general, and especially of the individual training.